Rheological and Mechanical Properties of TPU Composites Reinforced with Silver-Coated Copper Flakes (Annual Transactions of the Nordic Rheology Society, 2025)
The study investigates the preparation of conductive thermoplastic polyurethane (TPU) composites using a twin-screw extrusion, focusing on the effects of silver-coated copper (Cu@Ag) particles as conductive fillers. The rheological, mechanical, and electrical properties of the composites were characterized as a function of filler volume concentration. The rheological analysis enabled the determination of a percolating network formation, which is important both for processing the composites and for mechanical reinforcement in the solid state. With increasing Cu@Ag loading, the composites exhibited pronounced changes in viscoelastic behaviour. The results of the mechanical tests show that increasing filler concentration of the Cu@Ag filler in the TPU polymer affects the mechanical properties, i.e., an increase in the storage moduli (E′) and loss moduli (E'') was observed, resulting in a more brittle structure of the composite. Furthermore, the electrical conductivity increased sharply to 46.7 S/m at the highest filler concentration. The results showed that geometrical and electrical percolation thresholds were similar, occurring at ~15 vol.%. These results highlight the crucial role of filler loading in tailoring the conductive and viscoelastic properties of functional TPU composites.